Rancang Bangun Aplikasi Presensi Karyawan Berbasis Web Menggunakan Barcode Scanner - Anthoni Pulakiang; Fino C. Colling; Lanny Sitanayah (Jurnal RESTIKOM : Riset Teknik Informatika dan Komputer, 2024)
Set Jek North Sulawesi is an office that collaborates with the South Minahasa Cooperatives and Micro, Small and Medium Enterprises Service. Collecting employee attendance data at the Set Jek North Sulawesi Office still uses manual recording, where employees have to report to the staff on duty to collect incoming and outgoing attendance data. Recap of attendance reports is also carried out using manual recording and calculating the total number of employees who come in, go home, have permission, are sick, leave or are absent. Taking attendance and recapping attendance reports manually has shortcomings that can result in loss or damage to existing data. Another drawback is the lack of efficiency in processing employee attendance data. To overcome the problems that exist in the attendance taking section at the Set Jek North Sulawesi Office, we built a Web-Based Employee Attendance Application Using a Barcode Scanner. By using this application, the possibility of fraud can be avoided, because each employee must take their own attendance with a barcode scanner. This attendance application can also create employee attendance report recaps, so that manual calculations and recaps are no longer needed. The application will be designed using Data Flow Diagram and Entity Relationship Diagram. Then the application will be implemented using the PHP, HTML and JavaScript programming languages, and using MySQL as the database. The expected result is that this application can be an efficient solution for taking employee attendance at the Set Jek North Sulawesi Office.